Tuftsin Combines With Remyelinating Therapy and Improves Outcomes in Models of CNS Demyelinating Disease - Thompson, Kaitlyn K.; Nissen, Jillian C.; Pretory, Amanda; Tsirka, Stella E. (Frontiers in Immunology, 2018)
Though promoting remyelination in multiple sclerosis (MS) has emerged as a promising therapeutic strategy, it does not address inflammatory signals that continue to induce neuronal damage and inhibit effectiveness of repair mechanisms. Our lab has previously characterized the immunomodulatory tetrapeptide, tuftsin, which induces an anti-inflammatory shift in microglia and macrophages. This targeted anti-inflammatory agent improves physical deficits in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Here, we sought to determine whether tuftsin is also effective in combination with benztropine, an FDA-approved drug that stimulates remyelination, in both EAE and in the cuprizone model of demyelination. We show that combining these two agents to promote anti-inflammatory and remyelinating mechanisms alleviates symptoms in EAE and lessens pathological hallmarks in both MS models. Importantly, tuftsin is required to transform the inflammatory CNS environment normally present in EAE/MS into one of an anti-inflammatory nature, and benztropine is required in the cuprizone model to improve remyelination. Our data further support tuftsin’s beneficial immunomodulatory activity in the context of EAE, and show that when studying remyelination in the absence of an autoimmune insult, tuftsin still activated microglia towards an anti-inflammatory fate, but benztropine was necessary for significant repair of the damaged myelin. Overall, tuftsin effectively combined with benztropine to significantly improve MS-like pathologies in both models.